Strand 2: WWW-based tools for capturing on-line communications as an educational resource - Neilson, Irene; Smeaton, Calum (Proceedings of the International Conference on Networked Learning, 1998)
The WWW provides a rich communications interface to the Internee. To date, however, this infrastructure has been used primarily as a as a vehicle for the presentation of information. Only recently has the need to provide systems which engage students with Web based learning materials been recognised. In this paper, we argue the case for yet another level of software cool development: tools for the capture, archiving and retrieval of chose interactions which are taking place around the web based learning material. We suggest chat the communications in which students engage about Web based learning materials are of considerable educational value. They are the embodiment of the feedback that good teachers use to become better teachers in the traditional classroom situation. In the on-line environment, tools can be developed which capture, structure and make such dialogues available for inspection and interrogation thus creating a learning resource which grows naturally over time. Issues critical to the effective design of such systems are explored and one system, Organik, is described in detail.